Non-steroidal anti-inflammatory drug-induced anaphylaxis infrequent in 388 patients with mastocytosis: A two-center retrospective cohort study - Patrizia Bonadonna; Francesco Olivieri; Jesper Jarkvist; Francesca Nalin; Roberta Zanotti; Laura Maclachlan; Laura Maclachlan; Theo Gülen; Theo Gülen; Theo Gülen (Frontiers in Allergy, 2022)
BackgroundAnaphylaxis is a well-known feature of mastocytosis, particularly in relation to hymenoptera venom stings. It is therefore hypothesized that mastocytosis patients may also be predisposed to severe hypersensitivity reactions to certain medications including non-steroidal anti-inflammatory drugs (NSAIDs). For this reason, these patients are usually discouraged from using these drugs. The current study aimed to determine the prevalence and evaluate the severity of NSAID-related hypersensitivity reactions among patients with mastocytosis.MethodsA retrospective study was conducted among a total of 388 (≥18 years old) consecutive patients from two independent European mastocytosis centers, in Sweden and Italy. Patients underwent a thorough allergy work-up where self-reported NSAID-hypersensitivity reactions were re-evaluated by an allergist in the first cohort (202 patients) and results were validated in the second cohort (186 patients).ResultsOverall frequency of NSAID-hypersensitivity was 11.3% in the total study cohort. Most patients reacted with cutaneous symptoms (89%), whereas severe hypersensitivity reactions were infrequent with only 11 patients (2.8%) experiencing anaphylaxis. All NSAID-related hypersensitivity reactions had occurred before mastocytosis was diagnosed. There was no difference between the groups regarding gender, baseline tryptase levels or presence of atopy, asthma/rhinitis.ConclusionOur study indicates an approximate 4-fold increased prevalence of NSAID hypersensitivity among mastocytosis patients compared to the general population. However, most NSAID reactions were limited to the skin as the prevalence of overall anaphylaxis was infrequent. Our results support that mastocytosis patients with a known tolerance to NSAIDs can continue using these medications without special precautions, whereas those with a prior reaction to NSAIDs should undergo thorough allergy work-up, including drug challenges.